Localization of an epileptic orgasmic feeling to the right amygdala, using intracranial electrodes. (December 2018) - Chaton, Laurence; Chochoi, Maxime; Reyns, Nicolas; Lopes, Renaud; Derambure, Philippe; Szurhaj, William
Abstract: The limbic system has well-known functions in the regulation of human emotions and behaviour in general and sexual behaviour in particular. However, it is not clear which components of the limbic system are involved in orgasmic feelings. Although orgasmic aura can be elicited by direct electrical stimulation of the right mesial temporal lobe, the location of spontaneous and isolated orgasmic auras have not yet been reported in the literature. Here, we report on the first case of spontaneous orgasmic aura associated with a discharge in the right amygdala, following an investigation with depth electrodes in a woman with temporal lobe epilepsy. Her ictal orgasmic feeling reportedly felt the same as her physiological orgasms. This case sheds light on the amygdala's key role in human sexual function.